87.7k views
2 votes
3(5-2x)+9x=45 what is x

User Aakanksha
by
5.2k points

2 Answers

5 votes

Answer:

Note that ( − 9 x − 45 ) = ( − 9 ) ( x + 5 ) and that ( x 3 + 5 x 2 ) = ( x 2 ) ( x + 5 ) We can write x 3 + 5 x 2 − 9 x − 45 XXX = ( x 2 − 9 ) ( x + 5 ) If we further note that ( x 2 − 9 ) is the difference of squares ( x + 3 ) ( x − 3 ) we can expand this to x 3 + 5 x − 9 x − 45 XXX = ( x + 3 ) ( x − 3 ) ( x + 5 )

Explanation:

User Lordhong
by
5.4k points
1 vote

Answer:

10

Explanation:

Let's solve your equation step-by-step.

3(5−2x)+9x=45

Step 1: Simplify both sides of the equation.

3(5−2x)+9x=45

(3)(5)+(3)(−2x)+9x=45 (Distribute)

15+−6x+9x=45

(-6x+9x)+(15)=45 (Combine Like Terms)

3x+15=45 3x+15= 45

Step 2: Subtract 15 from both sides.

3x+15−15=45−153x=30

Step 3: Divide both sides by 3.

3/3=30/3

x=10

Answer:

x=10

User Shreeharsha
by
4.5k points